2015
DOI: 10.1007/s11356-015-4912-x
|View full text |Cite
|
Sign up to set email alerts
|

Permeable reactive barrier of coarse sand-supported zero valent iron for the removal of 2,4-dichlorophenol in groundwater

Abstract: In this study, coarse sand-supported zero valent iron (ZVI) composite was synthesized by adding sodium alginate to immobilize. Composite was detected by scanning electron microscope (SEM), X-ray diffraction (XRD), and X-ray fluorescence (XRF). SEM results showed that composite had core-shell structure and a wide porous distribution pattern. The synthesized composite was used for degradation of 2,4-dichlorophenol (2,4-DCP) contamination in groundwater. Experimental results demonstrated that degradation mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…The filling reactive material is chosen according to the type of contaminants to be removed. Iron metal, Fe (0) , is mainly used as a reactive media of PRBs acting by converting the contaminants, such as chlorophenols, nitrates and chlorinated hydrocarbons to non-toxic or immobile species (Lee et al, 2017;Gao et al, 2015;Chen et al , 2011). Organic materials are, instead, among the best reactive media to promote biological process for the remediation of other contaminants, such as nitrate and sulphate (Powell et al, 1998).…”
Section: Prbsmentioning
confidence: 99%
“…The filling reactive material is chosen according to the type of contaminants to be removed. Iron metal, Fe (0) , is mainly used as a reactive media of PRBs acting by converting the contaminants, such as chlorophenols, nitrates and chlorinated hydrocarbons to non-toxic or immobile species (Lee et al, 2017;Gao et al, 2015;Chen et al , 2011). Organic materials are, instead, among the best reactive media to promote biological process for the remediation of other contaminants, such as nitrate and sulphate (Powell et al, 1998).…”
Section: Prbsmentioning
confidence: 99%
“…2,4-Dichlorophenol (2,4-DCP), a priority pollutant, has been widely used in the production of insecticides, herbicides, flame retardants, and wood preservatives. It has become one of the most abundant chlorophenols (CPs) in aquatic environments around the globe due to its extensive use in agriculture and manufacturing . For instance, 2,4-DCP concentrations were reported to be 0–4.89 μg/L in river water in France, 0.1–6.72 μg/L in wastewater in Australia, 0.1–10 μg/L in river water in the Republic of South Africa, and 0.01–19.96 μg/L in surface water in China. Studies have shown that 2,4-DCP is an endocrine-disrupting chemical (EDC) that induces lipid accumulation, reactive oxygen species formation, and epigenetic programming and could impact the transcription levels of crucial genes in the hypothalamic–pituitary–gonadal (HPG) axis of zebrafish. In addition, 2,4-DCP exposure could also induce estrogenic effects, such as increased female ratio and vitellogenin (VTG) levels in zebrafish. However, the effects of 2,4-DCP on primordial germ cell (PGC) numbers, an important factor in zebrafish sex differentiation, remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%